Baseline clinical characteristics, comorbidities and prescribed medication in a real-world population of patients with idiopathic pulmonary fibrosis: the PROOF registry. Issue 1 (21st November 2018) - Wuyts, Wim A; Dahlqvist, Caroline; Slabbynck, Hans; Schlesser, Marc; Gusbin, Natacha; Compere, Christophe; Maddens, Sofie; Kirchgaessler, Klaus-Uwe; Bartley, Karen; Bondue, Benjamin
Abstract : Introduction: PROOF (a Prospective Observational Registry to Describe the Disease Course and Outcomes of Idiopathic Pulmonary Fibrosis) is an ongoing, observational registry initiated in 2013 with the aim of collecting real-world data from patients with idiopathic pulmonary fibrosis (IPF). Here, we present comprehensive baseline data, which were collected from patients on registry inclusion. Methods : Patients with IPF were enrolled across eight centres in Belgium and Luxembourg. Baseline data collected included demographics, diagnostic information and clinical characteristics, including lung function and health-related quality of life. Data on comorbidities and prescribed medication were also collected. Results : A total of 277 patients were enrolled in the PROOF registry. At inclusion, 92.8% and 6.5% of patients had a definite or probable diagnosis of IPF, respectively. Mean per cent predicted forced vital capacity and carbon monoxide diffusing capacity were 80.6% and 46.9%, respectively. Mean St. George's Respiratory Questionnaire total score was 47.0, and mean Cough-Visual Analogue Scale score was 30.5 mm. The most prevalent comorbidities reported at inclusion were gastrointestinal disorders (50.2%), including gastro-oesophageal reflux disease (47.3%) and metabolism and nutrition disorders (39.7%). At inclusion, 67.2% and 2.2% of patients were prescribed pirfenidone and nintedanib, respectively, with treatment initiated either prior to, or at the time of, inclusion. Medication prescribed concomitantly with pirfenidone included antihypertensives (54.8%), statins (37.1%) and prophylactic antithrombotics/anticoagulants (36.6%). Conclusion: The PROOF registry provides valuable demographic and clinical data from a real-world population of patients with IPF in Belgium and Luxembourg, demonstrating the high burden of comorbidities and prescribed medication in these patients. Longitudinal data from this patient population will be investigated in future analyses. Trial registration: PROOF is registered with the relevant authorities in Belgium and Luxembourg, with registration to Comité National d'Éthique et de Recherché (CNER) N201309/03 – 12 September 2013 and a notification to Comité National de Protection des Données (CNDP).